Analysis of Alternative to Kentucky Weight–Distance Tax. Issue 1 (January 2014) - Martin, Andrew; Bell, Mark; Walton, Jennifer
This study reviewed the existing literature on vehicle mileage taxes, details weight–distance tax repeal and replacement in other states, and provided a policy alternative to Kentucky's weight–distance tax. The authors developed a consolidation plan in which the International Registration Plan and intrastate license plate fees were increased by 129% and the weight–distance tax was eliminated. Revenue projections for the weight–distance tax and registration fees (for the current policy and its alternative) were compared to assess the impact on the state's road fund. In addition, the tax and fee liabilities for individual motor carriers were assessed to see whether the proposed changes would help or hurt firms of various sizes and operational tendencies. Interstate carriers that logged a high percentage of total miles on Kentucky roads or logged a low number of overall miles per vehicle would generally have seen an increased financial obligation to the state. Interstate carriers that logged a low percentage of total miles on Kentucky road or a high number of overall miles per vehicle would generally have seen a diminished financial obligation to the state. The vast majority of all intrastate carriers would have an increased financial obligation to the state under the proposed policy alternative. The study concluded with a discussion of the advantages and disadvantages of weight–distance tax elimination and replacement with a fee-based revenue structure.